Analysis of liquidity indicators: multicase study on the footwear sector in Brazil - Bicalho, Elton da Silva [UNESP]; Mannarelli Filho, Teucle [UNESP]; Goncalves, Luis Miguel Valente; Lucente, Adriano dos Reis [UNESP] (Sindicato Secretarias Estado Sao Paulo, 2023)
The footwear industry in Brazil plays a significant role in the country, both in terms of production, exports and job creation. This study aimed to analyze the economic and financial indicators of liquidity and, in addition, calculate and compare the Beta index of four Brazilian companies in the footwear sector listed on the Brazilian Stock Exchange -B3, during the period from 2012 to 2021. An exploratory qualitative analysis, which analyzed the liquidity indices and their possible relations with the Beta index, of four companies in the Brazilian footwear sector listed on B3, namely: Alpargatas SA, Cambuci SA, Grendene SA and Vulcabras SA. The results indicate adequate liquidity for all companies, and good payment capacity, with market-appropriate values and indicators. The proposed objectives were successfully achieved. However, it is important to highlight that the restriction of this study is limited to the analysis of the solvency of the selected companies, leaving out other relevant financial indicators, such as capital structure, profitability and indebtedness. Thus, new lines of research can be developed with the aim of exploring other economic and financial indicators.
Keywords: Footwear; Liquidity; Beta Index; Financial Indicators